TINGKAT KEPUASAN KELUARGA BERPENDAPATAN RENDAH TERHADAP SUMBERDAYA YANG DIMILIKI - Kusumo, Rani Andriani Budi; Simanjuntak, Megawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2009)
Family function as a system is very urged by what to be the aims of life and ownership of resources. Family’s aims can be reached when resources available. Satisfaction level on family’s resources ownership is influenced by family’s values. The aimed of this research were to identify the ownership of resources of low income family and to analyze the satisfaction level on resources ownership by low income family. This research was a cross sectional study in thirty poor families that lived in urban area. In low income family, resources ownership (especially physical resources) is limited. Average of income per capita per month was Rp 78.492,00. Income was used only for daily food consumption, just enough